Some Fixed Point Results in Fuzzy Strong b-Metric Space - Bhandari, Thaneshor; Manandhar, K. B.; Jha, Kanhaiya (Journal of Nepal Mathematical Society, 2024)
The theory of fixed points in pure mathematics is the most dynamics and active area of research activities. Also, the fuzzy metric space has been one of the important generalizations of usual metric space. As an extension of fuzzy metric space, the notion of fuzzy strong b-metric space has been introduced by Oner and Sostak in 2020. The purpose of this paper is to study the notions of fuzzy strong b-metric spaces and to establish some fixed point results in complete fuzzy strong b-metric space with examples. Our results extend and improve some well-known results in literature.